AN ELDER MISTREATMENT CARE MODEL: PATHWAYS FOR DISSEMINATION. (11th November 2018) - Dash, K; Stoeckle, R J; Bonner, A; Dyer, C B; Lachs, M S; Mosqueda, L; Lees, K E
Abstract: In this presentation we will present pathways for dissemination of a care model for addressing elder mistreatment in emergency department settings. We will describe our process of engaging representatives from related existing and emerging initiatives (e.g. Age Friendly Health Systems, NICHE, and Geriatric Emergency Department Guidelines), key federal agencies, and stakeholders from local communities to develop a plan for dissemination. Results from these efforts include the identification of key considerations for successful dissemination: 1) Identifying a point of entry with consideration for federal and state regulation, 2) engaging medical accreditation bodies, 3) creating associations with key champions and leading organizations, 4) identifying and assessing financial incentives, 5) aligning with existing technology, and 6) engaging key leaders and influencers. We will discuss these results and their implications for the piloting and evaluating the care model in emergency departments across the United States.